A study of saccadic eye movement dynamics in volleyball: comparison between athletes and non-athletes - Piras, A.; Lobietti, R.; Squatrito, S. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: Visual search strategy in sports may influence performance. Thus it is interesting to investigate oculo-motor behavior of athletes and its possible impingement upon sport training and coaching. The differences in fixations and saccadic eye movements between expert volleyball players and novice subjects was studied, by carrying out a precise analysis of gaze shifts during the observation of a standard game situation. METHODS: Fifteen professional athletes and fifteen non athletes watched at a volleyball filmed sequence in which a setter receives a pass tossed from the coach and sets it forward or backward. Then, the number and duration of fixations to specific interest areas (IAs) were counted. In addition, the sequences of saccades from each IA to the others were analyzed. RESULTS: The results showed that expert players performed fewer fixations of longer duration and spent more time looking first at the initial pass trajectory and then at the setter`s hands, disregarding the ball trajectory. The non athletes, instead, followed the whole course of the ball, before and after the hands touch. CONCLUSION: These findings support the interpretation that experts volleyball players extract more task-relevant information from each fixation than do less skilled athletes, and that player`s proficiency influences the strategy used in the treatment of visual information.